Iron-catalyzed asymmetric intramolecular cyclopropanation reactions using chiral tetramethyl-1, 1′-spirobiindane-based bisoxazoline (TMSI-BOX) ligands. Issue 5 (14th January 2019) - Gu, Haorui; Huang, Shaoying; Lin, Xufeng
Abstract : Fe complexes of TMSI-BOX based on the tetramethyl-1, 1′-spirobiindane backbone have been developed and applied in catalytic highly enantioselective intramolecular cyclopropanation reactions. Abstract : The versatile application of chiral bisoxazoline (BOX) ligands in diverse metal-catalyzed asymmetric reactions results in growing demand for novel BOX ligands containing different motifs. Herein, the successful development of a chiral spiro bisoxazoline ligand (TMSI-BOX) on the basis of the tetramethyl-1, 1′-spirobiindane motif and bisoxazoline chelating units is described. The corresponding Fe complexes of TMSI-BOX proved to be excellent catalysts in the asymmetric intramolecular cyclopropanation reaction of diazo derivatives, providing synthetically versatile [3.1.0]bicycloalkane derivatives bearing two contiguous quaternary chiral centers with high enantiomeric purity.